Zadovoljstvo z delom v javnem zavodu - Rape, Tamara (Socialno delo, 2010)
Some of the basic concepts relating to job satisfaction are discussed, such as planning work, motivational theories, burnout, personnel management, human reasources management and social work in working environment. A case study of a public institution in Slovenia was carried out in 2006. The institution is one of 62 similar institutions in which mostly social workers are employed. Social workers in this institution are least satisfied with their salary, volume of their work, working conditions and reputation of their work. On the other hand, they are very satisfied with the relations among co-workers and with freedom at work. Jov satisfaction is the analysed institution (compared with similar institutions) relatively low. Special aspects of dissatisfaction are discussed and some suggestions are proposed.
Keywords: zadovoljstvo pri delu; javni zavodi; social work; socialno delo; izgorevanje